2020
DOI: 10.1002/ecy.2945
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in benchmarking ecological null models: an assessment of current methods

Abstract: Identifying species interactions and detecting when ecological communities are structured by them is an important problem in ecology and biogeography. Ecologists have developed specialized statistical hypothesis tests to detect patterns indicative of community‐wide processes in their field data. In this respect, null model approaches have proved particularly popular. The freedom allowed in choosing the null model and statistic to construct a hypothesis test leads to a proliferation of possible hypothesis tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…We acknowledge the limitations associated with ecological null models (Molina and Stone, 2020) as well as our use of a strict taxonomic clustering threshold. First, null models applied to post‐competition pools can underestimate the influence of interspecific competition as the regional pool already reflects the effects of competition (Colwell and Winkler, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge the limitations associated with ecological null models (Molina and Stone, 2020) as well as our use of a strict taxonomic clustering threshold. First, null models applied to post‐competition pools can underestimate the influence of interspecific competition as the regional pool already reflects the effects of competition (Colwell and Winkler, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…5c). This underscores once more how inferring species interactions from snap-shots of co-occurrence patterns can be as hazardous as it is appealing, and requires careful thinking about null expectations (Blanchet et al, 2020; Molina and Stone, 2020; Münkemüller et al, 2020). We join the recent burst of cautionary articles in highlighting these concerns, and in any case, we encourage investigators to evaluate whether detected species association patterns could match those reported here, and so could stem from pure metacommunity dynamical effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well known that several pitfalls can compromise this approach, since correlation is not equivalent to interaction (Blanchet et al, 2020; Molina and Stone, 2020). As a simple example, patch heterogeneity and differential habitat preferences among species can cause species associations, even in the absence of any interaction between the pairs of species involved.…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, ecological null models are used by community ecologists to expose mechanisms of species interactions involved in species coexistence and patterns of biodiversity (e.g., Adler et al, 2010), and by evolutionary biologists to examine the role of competition in shaping natural selection on trait divergence (e.g., Anderson & Weir, 2021). Though ecological null models are traditionally used in explanatory inference, the same philosophy can be used to increase the rigor of predictive ecological inference (Dietze et al, 2018), and the identification of null models for specific types of data continues to be a topic of inquiry (Molina & Stone, 2020).…”
Section: Ecological Null Modelsmentioning
confidence: 99%